Impact of Protein-Enriched Plant Food Items on the Bioaccessibility and Cellular Uptake of Carotenoids - Mohammed Iddir; Juan Felipe Porras Yaruro; Emmanuelle Cocco; Emilie M. Hardy; Brice M. R. Appenzeller; Cédric Guignard; Yvan Larondelle; Torsten Bohn (MDPI AG, 2021)
Carotenoids are lipophilic pigments which have been associated with a number of health benefits, partly related to antioxidant effects. However, due to their poor solubility during digestion, carotenoid bioavailability is low and variable. In this study, we investigated the effect of frequently consumed proteins on carotenoid bioaccessibility and cellular uptake. Whey protein isolate (WPI), soy protein isolate (SPI), sodium caseinate (SC), gelatin (GEL), turkey and cod, equivalent to 0/10/25/50% of the recommended dietary allowance (RDA, approx. 60g/d), were co-digested gastro-intestinally with carotenoid-rich food matrices (tomato and carrot juice, spinach), and digesta further studied in Caco-2 cell models. Lipid digestion, surface tension and microscopic visualization were also carried out. Co-digested proteins positively influenced the micellization of carotenes (up to 3-fold, depending on type and concentration), especially in the presence of SPI (p < 0.001). An increased cellular uptake was observed for xanthophylls/carotenes (up to 12/33%, p < 0.001), which was stronger for matrices with an initially poor carotenoid micellization (i.e., tomato juice, p < 0.001), similar to what was encountered for bioaccessibility. Turkey and cod had a weaker impact. Significant interactions between carotenoids, lipids and proteins were observed during digestion. Co-digested proteins generally improved lipid digestion in all matrices (p < 0.001), especially for carrot juice, though slight decreases were observed for GEL. Protein impact on the surface tension was limited. In conclusion, proteins generally improved both carotenoid bioaccessibility and cellular uptake, depending on the matrices and carotenoid-type (i.e., carotene vs. xanthophylls), which may be relevant under specific circumstances, such as intake of carotenoid-rich food items low in lipids.